Effect of Starter Concentration and Fermentation Time on the Characteristics of Modified of Cassava Flour (Mocaf) - Dian Asykariyah Mauroh; Yeti Rusmiati Hasanah; Abdul Haris Mulyadi (Research in Chemical Engineering, 2023)
Mocaf (Modified Cassava Flour) is a modified cassava flour made through a fermentation process using microbes. One of the microbes that can be used for mocaf fermentation is Acetobacter xylinum . In this research, cassava tubers were fermented into mocaf flour with the help of a starter of Acetobacter xylinum bacteria. This research was conducted to determine the effect of starter A. xylinum's concentration and fermentation time on the characteristics of mocaf flour. The research method used OFAT (One Factor at A Time). The research consists of the making flour process (sorting, stripping, washing, slicing, fermentation, drying, milling, and sifting) and analyzing samples. The variations of starter A. xylinum concentration used were 5%, 10%, 15%, 20%, and 25%. While the variations of fermentation time were 24 hours, 36 hours, 48 hours, 60 hours, and 72 hours. The Parameters analyzed were % mass, moisture content, ash content, acid level, HCN content, and crude fiber content. The results showed that the starter concentration and fermentation time affected the percent mass (P-value <0.05). The mocaf flour that passes SNI is fermented cassava with a starter concentration of 15-25% and a fermentation time of 48-72 hours.